Analisis Perbedaan Penggunaan Electronic Control Unit (ECU) Standar dan Racing Terhadap Kinerja Mesin Sepeda Motor Injeksi - Kunto Hamijoyo; Dwiyanto Dwiyanto (Go Infotech: Jurnal Ilmiah STMIK AUB, 2026)
Electronic Control Unit (ECU) serves as the primary electronic component within the fuel-injected motorcycle combustion system, functioning to regulate fuel supply and ignition timing based on sensor parameters. This research aims to evaluate the performance differences of 150 cc fuel-injected motorcycles utilizing standard ECU versus racing ECU. The methodology employed involves experimental testing using a dynamometer to measure horsepower, torque, and Brake Specific Fuel Consumption (BSFC). The results indicate that the racing ECU is capable of increasing maximum horsepower by approximately 17% and torque by approximately 6% compared to the standard ECU. However, this performance enhancement is accompanied by an increase in fuel consumption of approximately 12%. This study provides a quantitative overview of the trade-off between performance improvements and fuel efficiency resulting from the application of racing ECU.